Surgery combined with intra-operative microwaves ablation for the management of colorectal cancer liver metastasis: A case-matched analysis and evaluation of recurrences - Guadagni, Simone; Marmorino, Federica; Furbetta, Niccolò; Carullo, Martina; Gianardi, Desirée; Palmeri, Matteo; Di Franco, Gregorio; Comandatore, Annalisa; Moretto, Roberto; Cecilia, Elisa; Dima, Giovanni; Masi, Gianluca; et al. (Frontiers in Oncology, 2022)
Purpose: Hepatic resection is the only chance of cure for a subgroup of patients with colorectal cancer liver metastasis (CRCLM). As the oncologic outcomesof intra-operative microwaves ablation (IMW) combined with hepatic resection still remain uncertain in this setting, we aimed to compare this approach with surgery alone in CRCLM patient’s candidate to metastases resection with radical intent. Methods: Using a case-matched methodology based on age, gender, ASA score, BMI and CRLM burden that take in consideration the number and maximum size of lesions, 20 patients undergoing hepatic resection plus IMW (SURG + IMW group) and 20 patients undergoing hepatic resection alone (SURG group), were included. Relapse-free Survival (RFS) and post-resection Overall Survival (OS) were compared between patients of two groups. Results: At the median follow up of 22.4±17.8 12/20 patients (60%) in SURG+IMW group and 13/20 patients (65%) in the SURG group experienced CRCLM recurrence (p=0.774).None of them had recurrence at the same surgical or ablation site of the first hepatic treatment. 7/12 patients in the SURG+IMW group and 7/13 patients in the SURG group underwent at least one further surgical treatment after relapse (p = 1.000). No difference was reported between the two groups in terms of RFS (p = 0.685) and post-resection OS (p = 0.151). The combined use of IMW was not an independent factor affecting RFS and post-resection OS at univariate and multivariate analysis. Conclusions: CRCLM patients undergoing surgery plus IMW have similar post-operative results compared with surgery alone group. The choice between the two approaches could be only technical, depending on the site, number and volume of the CRCLM. This approach could also be used in patients with CRCLM relapse who have alreadyundergone hepatic surgery